2020
DOI: 10.1155/2020/4097829
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cerebral Blood Flow Dynamics in Transient Ischemic Attacks Patients with Fast Cine Phase Contrast Magnetic Resonance Angiography

Abstract: Fast cine phase contrast magnetic resonance angiography (PC-MRA) has the potential to provide a quantitative measurement method for the diagnosis and treatment of cerebrovascular disease. To evaluation the changes of cerebral blood flow and the characteristics of artery lesion distribution in the patients of transient ischemic attacks (TIA). In all, 98 normal subjects and 106 TIA patients who underwent MRI examination within 72 h after the last symptom onset including the DWI sequence to exclude acute cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The study indicated that intracranial MRA combined with CU have high application value in the diagnosis of CI, and can effectively clarify vascular stenosis and hemodynamic characteristics of patients with CI. Wang et al 16 found that MRA examination can effectively characterize cerebral hemodynamic status in patients with cerebral ischemia. MRA allows to image arteries that are unreachable by a catheter approach, and the acquired images can be used to create specific cross-sectional views in the direction of choice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study indicated that intracranial MRA combined with CU have high application value in the diagnosis of CI, and can effectively clarify vascular stenosis and hemodynamic characteristics of patients with CI. Wang et al 16 found that MRA examination can effectively characterize cerebral hemodynamic status in patients with cerebral ischemia. MRA allows to image arteries that are unreachable by a catheter approach, and the acquired images can be used to create specific cross-sectional views in the direction of choice.…”
Section: Discussionmentioning
confidence: 99%
“…This allows to clearly observe changes in the outer wall and lumen of blood vessels, and to present the distribution of atherosclerotic plaques, determine their size, and accurately evaluate the condition of carotid artery stenosis. 16 , 17 98 normal subjects and 106 TIA patients who underwent MRI examination within 72 h after the last symptom onset including the DWI sequence to exclude acute cerebral infarction were enrolled. The blood flow of the cranial total, the area of the internal carotid artery and vertebral artery, the average velocity, and the average blood flow were obtained and compared in normal subjects and TIA group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings align with the hemodynamic changes observed prior to TIA infarction ( 6 ) and are consistent with previous reports. Additionally, the majority of TIA patients exhibited varying degrees of vascular stenosis or occlusion ( 22 ). Analysis of the best CTA images obtained through WB-CTP examination in these patients identified 278 responsible vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative MRA has been shown to be useful in the assessment of a variety of flow-limiting cerebrovascular conditions [14][15][16][17][18][19][20][21][22] and has been validated as a primary tool to assess stroke risk in vertebrobasilar insufficiency. 23 To the best of our knowledge, our study is the first to report the use of QMRA in cerebral vasospasm after SAH.…”
Section: Discussionmentioning
confidence: 99%